A conceptual model of the strategic alliance process: from initiation to conclusion. (3rd December 2009) - Adnan, Syed M.; Ramanathan, Krishnamurthy; Turpin, Tim; Chapman, Ross L.
The primary focus of this paper is to present a conceptual model of the strategic alliance process that delineates the stages of initiation, formation and sustained operation of strategic alliances. Based on a detailed review of the literature, the model takes a process perspective and explicitly focuses on the key factors that influence the outcomes and behaviour of an alliance during these stages. The model provides insights to both policy-makers and alliance managers on establishing and managing successful alliances. Based on different aspects of the model, the possible hypotheses have been developed related to the initiation, formation and operation of strategic alliances. The approaches that are currently under way to test these hypotheses are described and the possible practical implications of the findings that could emerge are also discussed.